Ritualizing secular space: a waste management facility on Bloemfontein's northern landfill - Steyn, Joubert (University of the Free State, 2022)
This thesis explores an architectural solution to the complex issue of landfilling in the urban environment. However, the aim is to transcend functionalistic recycling and offer more than mere site rehabilitation. How can an architectural intervention mitigate ruination and empower the marginalized as a form of social justice in response to neglected spaces? Traditional recycling methods are often too costly or cumbersome for degraded and contaminated plastic samples from landfills. Plastic refuse can be more efficiently recycled through a waste management technique called pyrolysis, which can turn plastic into fuel sources, stimulating economic growth and addressing fuel shortages. Good architecture is much more than a programmatic accommodation list; it has a layeredness that adds depth and presents rich opportunities for design intervention. How can a waste management facility become more than just a piece of infrastructure? The hopes and aspirations for this thesis, captured in this document, are to perform architectural alchemy on the urban environment, to transform a failing landfill in the northern suburbs of Bloemfontein into an urban node that can actively contribute to the local community and become worth its weight in gold.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2022